Tobacco Control Policy in the Netherlands Between Economy, Public Health, and Ideology - Willemsen, Marc C. (Palgrave Studies in Public Health Policy Research, 2018)
Governments have known since the 1960s that smoking results in irreversible health damage. This open access book examines why governments have done so little to combat this when they have been aware of the problem and its solutions for decades. What are the strategies and decisions that make a difference, given that policy environments are often not conducive to change? Taking the Netherlands as an example, this book helps to understand the complex policy process at the national level and why it so often appears irrational to us. It is the most sophisticated analysis of tobacco control policy to date, applying insights from political sciences to the field of tobacco control. Marc C. Willemsen is Professor of Tobacco Control Research at the Department of Health Promotion, University of Maastricht, the Netherlands. He started tobacco research in 1989 and has since become a recognised expert in the field of tobacco control. He wrote and contributed to numerous research studies and scientific papers. In addition to his academic work, he gained first hand insights into the policy making process while working for various national tobacco control organisations. .